Status and influential factors of vitamin D among children aged 0 to 6 years in a Chinese population - Heng Zhang; Zhijuan Li; Yarong Wei; Jinyan Fu; Yaling Feng; Daozhen Chen; Dexiang Xu (BMC, 2020)
Abstract Background Vitamin D insufficiency and deficiency in childhood are common. However, the status and influential factors of vitamin D during different ages are not clear. This study aimed to survey vitamin D concentrations in children aged 0 to 6 years and explore its influential factors. Methods A total of 6953 children were recruited in Wuxi City of East China from January to December in 2016. Enzyme-linked immunosorbent assay was used to determine the serum concentrations of 25-hydroxyvitamin D [25(OH)D]. Results The median vitamin D concentrations in the infant group (0-1 years of age) was 69.40 nmol/L, which were higher than that in both the toddlerhood group (1-3 years of age; 62.30 nmol/L) and the preschool group (3-6 years of age; 50.85 nmol/L). In addition, the median vitamin D concentrations were 71.70 nmol/L in summer, which was higher than that in spring (64.25 nmol/L), autumn (62.95 nmol/L) and winter (64.10 nmol/L). However, no difference was observed between genders (P = 0.974). Furthermore, the prevalence of vitamin D deficiency (< 50 nmol/L) was 48.1% in the preschool group (3-6 years of age), which was higher than the 21.2% vitamin D deficiency in the toddlerhood group (1-3 years of age) and the 17.9% vitamin D deficiency in the infant group (0-1 years of age). Interestingly, a nonlinear association between 25(OH) D and air temperature was observed. Conclusions A high prevalence of vitamin D deficiency was common in a Chinese population of children 0-6 years old, especially in the preschool-aged children. Therefore, we suggested that we should pay more attention to vitamin D supplementation in Chinese young children.